1982
DOI: 10.1111/j.1570-7458.1982.tb03208.x
|View full text |Cite
|
Sign up to set email alerts
|

VIRULENCE TO RICE CULTIVARS AND SELECTION FOR VIRULENCE IN POPULATIONS OF THE BROWN PLANTHOPPER NILAPARVATA LUGENS

Abstract: Biotype 1, 2 and 3 populations from the Philippines were selected for 11 generations on 3 standard rice cultivars, TN1 (no gene for resistance). Mudgo (Bph 1). and ASD7 (bph 2). Percentage survival, weight of newly emerged ♀ ♀ and time taken for 50°C of survivors to become adults were scored for each line at each generation and combined into a single index. Virulence was assessed before and after 10 generations of selection by measuring weight change and weight of honeydew produced by ♀ ♀ in 24 hr. Performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 5 publications
7
48
0
1
Order By: Relevance
“…Local BPH populations from different rice varieties in the different places in Sri Lanka showed different virulence patterns and specific adaptation to the respective local host rice plants, on which they fed and reproduced (Claridge and den Hollander 1982). Interestingly, a perennial wild rice Oryza rufipogon is universally susceptible to all the local BPH populations.…”
Section: Genetic Flexibility In the Bph Biotype Populationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Local BPH populations from different rice varieties in the different places in Sri Lanka showed different virulence patterns and specific adaptation to the respective local host rice plants, on which they fed and reproduced (Claridge and den Hollander 1982). Interestingly, a perennial wild rice Oryza rufipogon is universally susceptible to all the local BPH populations.…”
Section: Genetic Flexibility In the Bph Biotype Populationsmentioning
confidence: 98%
“…Present BPH populations in Southeast Asia exhibit complicated variations in their virulence patterns depending upon the history of rice variety shifts in each locality, where genefor-gene patterns are no longer recognized between the BPH populations and rice varieties (Claridge and den Hollander 1982).…”
Section: Varietal Resistance-breaking Planthopper Biotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study conducted at about the same time and using a different N. lugens population virulent to the same Bph1 gene, identified a different 'virulence gene' and associated 'virulence QTLs' [48]. Furthermore, previous studies have indicated the role of regional adaptation by planthoppers to locally popular rice varieties: for example, Claridge and Den Hollander [19] have shown that N. lugens from Australia had poor survival on the highly susceptible Asian variety TN1. Furthermore, Claridge et al [20] indicated that N. lugens populations from Sri Lanka had highest fitness when reared on varieties from the regions where each population was originally collected, but had low fitness on varieties from other regions.…”
Section: Origins Of Resistance and Local Adaptationmentioning
confidence: 99%
“…Such a biotype of the brown planthopper, Nilaparvata lugens, was observed after resistant varieties of rice were cultivated for a few years (Sogawa, 1982;Gallagher et al, 1994). Several studies showed that N. lugens populations have genetic variation in virulence to resistant rice varieties using artificial selection in the laboratory (den Hollander and Pathak, 1981;Ito and Kisimoto, 1981;Claridge and den Hollander, 1982) and quantitative genetic analysis (Tanaka, 1999). The artificial selection of biotypes was also carried out in the green leafhopper, Nephotettix virescens Takita and Habibuddin, 1985).…”
Section: Introductionmentioning
confidence: 99%